Analysis of the expression of porcine CD200R1 and CD200R1L by using newly developed monoclonal antibodies. (November 2019) - Poderoso, T.; Martínez de la Riva, P.; Uenishi, H.; Alvarez, B.; Toki, D.; Nieto-Pelegrín, E.; Alonso, F.; Domínguez, J.; Ezquerra, A.; Revilla, C.
Abstract: CD200R1 and CD200R1-like are paired receptors which modulate activation of immune cells. Here, we describe the characterisation of their porcine homologues. Analysis of database porcine sequences shows an exceptionally high homology between the extracellular Ig-like domains of these receptors, being the rest more dissimilar. We have obtained two mAbs, PCT1 and PCT3, against a CD200R1-Fc recombinant protein, that bind on CHO cells expressing GFP-tagged CD200R1. The specificity of these mAbs was analysed on CD200R1 L, and also on a CD200R1 splicing variant that lacks the V-type Ig domain. PCT1 bound to both CD200R1 and CD200R1L, but not to the splicing variant, what suggests that recognises an epitope in the V-type Ig domain. PCT3 reacted with both CD200R1 variants, but not CD200R1L, probably binding to an epitope in the N-terminal sequence of CD200R1. Analysis of porcine cells with these mAbs showed expression of CD200R1/CD200R1L on B cells, monocytes and alveolar macrophages. Highlights: Porcine CD200R1 and CD200R1L show a single amino-acid difference in their Ig-like domains. PCT1 and PCT3 mAbs discriminate between porcine CD200R1 and CD200R1L PCT1 mAb binds both CD200R1 and CD200R1L while PCT3 mAb only reacts with CD200R1. These mAbs stain monocytes, a subset of B lymphocytes and alveolar macrophages.